Preliminary Study on Fe(III) Detection Using Nitrogen-Doped Carbon Quantum Dots via HSV-Based Smartphone Fluorescence Analysis - Agustina, Erika; Damayanti, Wulan Amalia Mustika; Aji, Abdul; Ghifari, M Alvien (Indonesian Journal of Chemical Analysis (IJCA), 2025)
This study successfully synthesized nitrogen-doped carbon quantum dots (N-CQDs) from banana peel waste via a hydrothermal method using urea as the nitrogen source. FTIR and optical characterization confirmed the presence of hydroxyl, carbonyl, and amine functional groups, along with distinct photophysical features, including an absorption peak at 304 nm, excitation at 392 nm, and blue fluorescence emission at 465 nm. Upon Fe(III) exposure, the N-CQDs exhibited selective fluorescence quenching and a measurable hue (H) value shift. A linear relationship was observed between hue and Fe(III) concentration in the 1-5 mM range (R2 = 0.9822). The limit of detection (LOD) and limit of quantification (LOQ) were estimated at 0.948 mM and 2.875 mM, respectively. These findings demonstrate the potential of banana peel-derived N-CQDs as a low-cost, environmentally friendly, and smartphone-compatible fluorescence probe for Fe(III) detection in aqueous environments